Evaluation of Cinnamomum osmophloeum Kanehira Extracts on Tyrosinase Suppressor, Wound Repair Promoter, and Antioxidant - Man-Gang Lee; Su-Yu Kuo; Shih-Yu Yen; Hsia-Fen Hsu; Chung-Hang Leung; Dik-Lung Ma; Zhi-Hong Wen; Hui-Min David Wang (The Scientific World Journal)
Cinnamomum osmophloeum Kanehira belongs to the Lauraceae family of Taiwan’s endemic plants. In this study, C. osmophloeum Kanehira extract has shown inhibition of tyrosinase activity on B16-F10 cellular system first. Whether extracts inhibited mushroom tyrosinase activity was tested, and a considerable inhibition of mushroom tyrosinase activity by in vitro assays was presented. Animal experiments of C. osmophloeum Kanehira were carried out by observing animal wound repair, and the extracts had greater wound healing power than the vehicle control group (petroleum jelly with 8% DMSO, w/v). In addition, the antioxidant capacity of C. osmophloeum Kanehira extracts in vitro was evaluated. We measured C. osmophloeum Kanehira extract’s free radical scavenging capability, metal chelating, and reduction power, such as biochemical activity analysis. The results showed that a high concentration of C. osmophloeum Kanehira extract had a significant scavenging capability of free radical, a minor effect of chelating ability, and moderate reducing power. Further exploration of the possible physiological mechanisms and the ingredient components of skincare product for skin-whitening, wound repair, or antioxidative agents are to be done.